2011
DOI: 10.1016/j.molimm.2011.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of caveolin-1 in the Jak–Stat signaling pathway and infectious spleen and kidney necrosis virus infection in mandarin fish (Siniperca chuatsi)

Abstract: Caveolae, the major source of caveolin-1 protein, are specialized invaginated microdomains of the plasma membrane that act as organizing centers for signaling molecules in the immune system. In the present study, we report the cloning and characterization of caveolin-1 (mCav-1) from mandarin fish (Siniperca chuatsi) and study on the roles of mCav-1 in the fish Jak-Stat signaling pathway and in virus infection. The cDNA sequence of mCav-1 was 707bp in size, encoding a protein of 181 amino acids, which was diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 71 publications
1
24
0
Order By: Relevance
“…Interestingly, TLR3-dependent polyinosinic-polycytidylic acid-induced gene expression of SOCS3 is down-regulated in mandarin fish (Siniperca chuatsi) following expression of the scaffold domain of a caveolin-1 homologue [26]. As such, structural components of caveolae might be involved in the regulation of cytokine signalling at several levels.…”
Section: Caveolae Camp and Inflammatory Signallingmentioning
confidence: 99%
“…Interestingly, TLR3-dependent polyinosinic-polycytidylic acid-induced gene expression of SOCS3 is down-regulated in mandarin fish (Siniperca chuatsi) following expression of the scaffold domain of a caveolin-1 homologue [26]. As such, structural components of caveolae might be involved in the regulation of cytokine signalling at several levels.…”
Section: Caveolae Camp and Inflammatory Signallingmentioning
confidence: 99%
“…29,30 Because caveolin-1 has been demonstrated to regulate β1-integrin signaling, 31 we can speculate that caveolin-1 also modulates β2-integrins to influence differentiation. Also, as the transcription factor IRF-8/ICSBP has been identified as a regulator of macrophage maturation 32 and caveolin-1 has been reported to influence its activation through the Janus kinase/signal transducers and activators of transcription signal pathway, 33 this may be another means by which caveolin-1 influences differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…MFF-1 cells were maintained in DMEM supplemented with 10% FBS and passaged every 3 to 4 days via trypsinization in monolayer cultures at 27°C under a humidified atmosphere of 5% CO 2 (27). Rabbit polyclonal anti-MCP, anti-ORF101L, and anti-mCav-1 and mouse polyclonal anti-mCav-1 antisera were previously generated in our laboratory (26). Mouse monoclonal antibodies (Abs) raised against ␣-actin, the Flag tag, the green fluorescent protein (GFP) tag, the glutathione S-transferase (GST) tag, the maltose-binding protein (MBP) tag, ␤-tubulin, and the V5 tag were obtained from Sigma-Aldrich (St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported that ISKNV may internalize into mandarin fish fry (MFF-1) cells through a caveola-dependent endocytic pathway (25,26). We postulated that certain ISKNV proteins may interact with mandarin fish Cav-1 (mCav-1).…”
mentioning
confidence: 99%